1998
DOI: 10.1016/s0896-6273(00)80589-9
|View full text |Cite
|
Sign up to set email alerts
|

Homer Binds a Novel Proline-Rich Motif and Links Group 1 Metabotropic Glutamate Receptors with IP3 Receptors

Abstract: Group I metabotropic glutamate receptors (mGluRs) activate PI turnover and thereby trigger intracellular calcium release. Previously, we demonstrated that mGluRs form natural complexes with members of a family of Homer-related synaptic proteins. Here, we present evidence that Homer proteins form a physical tether linking mGluRs with the inositol trisphosphate receptors (IP3R). A novel proline-rich "Homer ligand" (PPXXFr) is identified in group 1 mGluRs and IP3R, and these receptors coimmunoprecipitate as a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
682
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 801 publications
(699 citation statements)
references
References 65 publications
15
682
0
2
Order By: Relevance
“…The EVH1 domain exhibits a high degree of similarity across Homer isoforms and is essential for Homer interactions with a proline-rich sequence (PPSPF) displayed by proteins regulating drug-induced alterations in neuronal morphology, synaptic architecture, and glutamate receptor signaling/intracellular calcium dynamics. Of particular relevance to drug-induced neuroplasticity [e.g., 20,73,74,[78][79][80][81][82][89][90][91][92][93][94][95][96][97][98][99][100][123][124][125][126][127][128][129][130], these proteins include the mGluR1a and mGluR5 subtypes of Group 1 metabotropic glutamate receptors (mGluRs) [34,102,104,107,[131][132][133][134][135][136][137], the NMDA glutamate receptor scaffolding protein Shank [38,132,138,139], the inositol-1,4,5-triphosphate (IP3) receptor, a down-stream mediator of Group1 mGluR signaling [133,[140]…”
Section: Molecular Aspects Of Homer Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The EVH1 domain exhibits a high degree of similarity across Homer isoforms and is essential for Homer interactions with a proline-rich sequence (PPSPF) displayed by proteins regulating drug-induced alterations in neuronal morphology, synaptic architecture, and glutamate receptor signaling/intracellular calcium dynamics. Of particular relevance to drug-induced neuroplasticity [e.g., 20,73,74,[78][79][80][81][82][89][90][91][92][93][94][95][96][97][98][99][100][123][124][125][126][127][128][129][130], these proteins include the mGluR1a and mGluR5 subtypes of Group 1 metabotropic glutamate receptors (mGluRs) [34,102,104,107,[131][132][133][134][135][136][137], the NMDA glutamate receptor scaffolding protein Shank [38,132,138,139], the inositol-1,4,5-triphosphate (IP3) receptor, a down-stream mediator of Group1 mGluR signaling [133,[140]…”
Section: Molecular Aspects Of Homer Proteinsmentioning
confidence: 99%
“…Exons 6-10 encode the carboxy-tail of the majority of Homer proteins that consists of a coiled-coil (CC) domain, 2 leucine zipper motifs and encode also the 3′ UTR [104,105,107]. Homer proteins multimerize through CC/ leucine zipper motif interactions [104,105,107,133,143,144] and a recent elucidation of the quaternary structure of Homers indicate that these proteins form tetramers with each monomer oriented in parallel [143]. The tetrameric structure of Homer oligomers confers slower turnover rates and greater efficiency of localization to dendritic spines [143].…”
Section: Molecular Aspects Of Homer Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both long and short Homer isoforms interact through an Ena/VASP1 homology (EVH1) domain with a long proline-rich motif located on Group 1 metabotropic glutamate receptors (mGluRs), inositol-1,4,5-triphosphate (IP3) and ryanodine receptors, TRP cation channels and Shank (Brakeman et al, 1997;Hwang et al, 2003;Kammermeier et al, 2000;Kato et al, 1998;Tu et al, 1998Tu et al, , 1999Xiao et al, 1998;Yuan et al, 2003). Long Homer isoforms contain a coiled-coil (CC) domain at their Cterminus that enables the cell membrane localization and clustering of glutamate receptors and proteins involved in their intracellular signaling cascades (Abe et al, 2003;Naisbitt et al, 1999;Rong et al, 2003;Shiraishi et al, 2003a, b).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence has demonstrated that neurotransmitter receptors (Sheng and Pak 1999) and molecules involved in the second messenger system (Chen et al 1998;Kim et al 1998;Tu et al 1998;Wu and Cline 1998) are targeted to specific subcellular domains. In the cAMP signal transduction pathway, PKA was found to be targeted to glutamate receptors and synapses (Carr et al 1992;Colledge et al 2000).…”
mentioning
confidence: 99%